A mechanistic understanding of surface Bi enrichment in dilute GaBi systems. Issue 26 (28th June 2021) - Lambie, Stephanie; Steenbergen, Krista G.; Gaston, Nicola
Abstract : Migration of an internal Bi toward a surface Bi island through six distinct regimes in dilute GaBi alloys is shown. Surface Bi patterning is anticorrelated with the migration of the internal Bi to the surface. Abstract : Experiment has shown that dilute GaBi systems produce a range of self-organised nanostructured patterns at the surface [Tang et al., Nat. Nanotechnol., 2021, 16, 431–439]. Using extensive ab initio molecular dynamics simulations, we elucidate the mechanisms underlying the formation of the Bi surface islands in Bi-doped Ga liquid metals. Here, we show that in order for internal Bi atoms to diffuse to the surface a lateral extension of the Ga surface network is required. Furthermore, the absence of surface Bi patterning perturbs the Ga surface network providing a preferred path for an internal Bi to diffuse. By understanding how and why Bi nucleates at a surface, we increase the ability to control, manipulate and design such systems for use in future electronic devices.